Multiple Religious Belonging among Congregation Members of the United Indonesian Jewish Community and Sha’ar Hashamayim Synagogue - Maulana, Abdullah Muslich Rizal (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
This research aimed to elaborate on the Indonesian Jewish community, represented by The United Indonesian Jewish Community led by Rabbi Benjamin Meijer Verbrugge and Sha'ar Hashamayim Synagogue under the spiritual guidance of Rabbi Yaakov Baruch. This research followed the theoretical framework of multiple religious belonging (MRB), pioneered by Catherine Cornille (1961–). This research combined primary data from in-depth interviews conducted offline and online with congregation members of both communities, as well as an extensive literature review. This research commenced its analysis by considering the conflicting religious identities of Indonesian Jews within their Indonesian identity card (Kartu Tanda Penduduk, abbreviated KTP in Bahasa Indonesia), which eventually investigated the identity of Indonesian Jews. This research concluded that MRB’s scientific schema, consisting of elements of Cultural Belonging, Family Belonging, Situational Belonging, Believing without Belonging, and Asymmetrical Belonging, may not fit entirely to the theological concern of Indonesian Jews, yet some of its elements may fit into a more secular, lower, context of ‘Civil’ Identity. The ambiguity of the existence of Indonesian Jews prevails because they are Jewish, practising Jewish rituals, and firmly committed to Jewish tradition, yet cannot conceal their Jewish identity fully in their KTP. Further investigation concerning their level of religiosity and how their Jewishness is practiced may invite further research.